2020
DOI: 10.1016/j.ijpsycho.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The error-related negativity (ERN) moderates the association between interpersonal stress and anxiety symptoms six months later

Abstract: Anxiety disorders are often preceded by interpersonal stress; however, most individuals who experience stress do not develop anxiety, making it difficult to predict who is most susceptible to stress. One proposed trans-diagnostic neural risk marker for anxiety is the error-related negativity (ERN), a negative defection in the event-related potential waveform occurring within 100 ms of error commission. The present study sought to investigate whether interpersonal stress experienced over the course of a year in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 138 publications
2
28
0
Order By: Relevance
“…Loss and Gain at Cz ( Banica et al, 2020). Another study found a similar effect in children exposed to a natural disaster (Meyer et al, 2017), and in a study of adults, a heightened ERN prior to the COVID-19 pandemic was indirectly associated with increases in symptoms during the first COVID-19 wave, through effects on perceived risk and stress (Riesel et al, 2021).…”
Section: Errorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Loss and Gain at Cz ( Banica et al, 2020). Another study found a similar effect in children exposed to a natural disaster (Meyer et al, 2017), and in a study of adults, a heightened ERN prior to the COVID-19 pandemic was indirectly associated with increases in symptoms during the first COVID-19 wave, through effects on perceived risk and stress (Riesel et al, 2021).…”
Section: Errorsmentioning
confidence: 86%
“…There is emerging evidence that an enhanced neural response to errors makes people particularly susceptible to adverse effects of stressors. For instance, one recent study showed that among first-year undergraduates who experienced a large number of stressors across the course of their first year, students with a larger ERN at entry to university were more likely to show heightened anxiety by the end of the year than those who had a smaller ERN at baseline (Banica et al, 2020). Another study found a similar effect in children exposed to a natural disaster (Meyer et al, 2017), and in a study of adults, a heightened ERN prior to the COVID-19 pandemic was indirectly associated with increases in symptoms during the first COVID-19 wave, through effects on perceived risk and stress (Riesel et al, 2021).…”
Section: Errorsmentioning
confidence: 99%
“…Worries about academic performance lead to dual stresses upon students' mental health (6). A volume of literature found that anxiety mostly followed a stressful event (7)(8)(9)(10). Previous research found that compared with objective stress, subjective stress could better predict the mental health of college students (11).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between heightened error monitoring, as indexed by a larger (i.e., more negative) ERN, and greater anxiety has been demonstrated both concurrently and longitudinally, such that a larger ERN predicts greater anxiety later in development ( 16 , 17 ). Although longitudinal data remain scarce and the effects are relatively weak, the available evidence suggests that individuals with an elevated ERN are prone to heightened anxiety following high levels of stress ( 18 , 19 ), such as natural disasters [e.g., Hurricane Sandy ( 19 )]. Together, these findings suggest that heightened error monitoring may predict increased anxiety during the COVID-19 pandemic.…”
mentioning
confidence: 99%